A mixed-methods evaluation of an intervention for enhancing alcohol screening in adults aged 50+ attending primary health care - Towers A; Newcombe D; White G; McMenamin J; Sheridan J; Rahman J; Moore A (CSIRO Publishing on behalf of The Royal New Zealand College of General Practitioners, 2025)
Introduction Adults aged 50 years and over are drinking more than ever but primary health care (PHC) professionals find it challenging to screen them for alcohol-related harm, despite being at greater risk for harm than younger drinkers. Aim This intervention aimed to enhance alcohol screening for this cohort by (a) introducing an algorithm in the patient management system to automate detection of alcohol risk in patients and (b) providing training to support health professionals' practice of, knowledge about, and comfort with alcohol screening in this cohort. Methods Eleven PHC practices in Aotearoa New Zealand took part in this intervention, including 41 PHC health professionals. Development and integration of the automated alcohol screening process within PHC patient management systems was undertaken in parallel with health professional training approaches. Results Screening rates increased substantially at intervention initiation but fell immediately with the onset of the New Zealand COVID-19 national lockdown. Two-thirds of health professionals identified the system screening prompts, over 40% felt this changed their screening practice, and 33% increased their awareness of - and felt more comfortable screening for - alcohol-related risk in those aged 50+. Discussion We illustrated an initial increase in alcohol screening rates in those aged 50+ as a result of this intervention, but this increase could not be sustained in part due to COVID-19 disruption. However, health professionals indicated that this intervention helped many change their practice and enhanced their awareness of such risk and comfort in screening for alcohol-related risk in those aged 50+.
Keywords: Ageing; Alcohol; General practitioners; Primary health care; Professional education; Screening